Alternatives risk behavior intervention in high school students - Álvarez-Trujillo, Estefanía (2020)
Risk behaviors are actions that involucrate danger to the person, mainly in an adolescence. For this reason, the objective of this article is to offer intervention alternatives about risk behavior in high school students to favor the integral formation. In this study, it elaborate a diagnostic that it view the situation of the educative institution about risk behavior of these students. It interviewed 10 people, including teachers and administrators, and it to survey 205 students belonging to the Industrial Technological and Services Baccalaureate Center in Villahermosa, Tabasco, Mexico in November 2019, using the action research method. Some results of this research indicates that there are various risk behaviors in the institution, but there are no intervention strategies that allow them to be attended it.